How Best to Use the Extraordinary Hydrocarbon Revenues in Bolivia: Results from a Computable General Equilibrium Model - Lykke E. Andersen (Institute for Advanced Development Studies (INESAD), 2006)
The high oil prices and the sharp increases in royalties mean that the natural gas boom in Bolivia has become very important for the economy, and particularly important as a source of government revenues. Using a CGE model, Andersen et al (2006) show that the natural gas boom is likely to boost GDP growth by about 1 percentage point per year. However, if the government continues with past spending and investment patterns, the boom is also likely to have a very adverse effect on the income distribution, so much so that the poorest half of the population is likely to experience absolute reductions in their real income levels compared to a scenario without gas boom. The present paper explores alternative uses of natural gas revenues in the CGE model to see if a better outcome can be engineered.
Keywords: Q33; Q43; 330; Natural Gas; Inequality; CGE model; Bolivia